PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Lumbangaol, Romasi; Siregar, Cindyloisa (UNIKA Santo Thomas, 2023)
This study aims to determine the effect of disclosure of Corporate Social Responsibility, Profitability (ROA) and Leverage on Tax Aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study was obtained by purposive sampling, with a total sample of 39 companies with a period of 3 years so that the total was 117. The analytical method used was multiple linear regression and hypothesis testing using the t test and F test with a significant level of 5%. The results of this study indicate that Corporate Social Responsibility (CSR) has no effect on tax aggressiveness, profitability has no effect on tax aggressiveness, and leverage has a positive and significant effect on tax aggressiveness. Simultaneous test results show that Corporate Social Responsibility (CSR), Profitability and Leverage have a significant effect on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange.